A non-invasive technique for monitoring supply voltage variation to single phase induction motor using doppler UWB radar signal analysis - Barusu, Madhusudhana Reddy; Rani, Nalubolu Geetha; Reddy, Yeramareddy Venkata Siva; Reddy, Gongati Pandu Ranga (Institute of Advanced Engineering and Science, 2024)
The induction motors (IMs) are important components of various industries. The condition of IMs monitored continuously using contact and non-contact methods continuously. The contact methods are expensive, complex and difficult to implement. This paper proposes a non-contact method of fault identification in the single-phase induction motor operating in different conditions by analyzing doppler ultra-wide band (UWB) radar signal. The UWB radar generates a high frequency signal, which is transmitted on to the Induction motor form transmitter and software phase locked loop (SPLL) condition received signal from the receiver. The PLL implements as low pass filter, receives reflected signal from an induction motor along with high frequency noise. The received signal filtered to remove the high frequency noise and filtered output is analyzed to identify the different faults such as over voltage faults and under voltage faults when the motor is running with high, medium and low speed. The proposed non-invasive method has advantages compared to other such as the sensor’s sensitivity will not affect with motor temperature and accuracy will not change with position of the sensor and presence of other machines.